Prehospital Vasopressor Use Is Associated with Worse Mortality in Combat Wounded. (23rd February 2021) - Fisher, Andrew D.; April, Michael D.; Cunningham, Cord; Schauer, Steven G.
Abstract: Introduction: Vasopressor medications are frequently used in the management of hypotension secondary to shock. However, little data exists regarding their use in hypotensive trauma patients and their use is controversial. Methods: The Department of Defense Trauma Registry was queried from January 2007 to August 2016 using a series of procedural codes to identify eligible casualties, which has been previously described. Mortality was compared between hypotensive casualties with documentation of receipt of vasopressor medications versus casualties not receiving vasopressors. To control for potential confounders, comparisons were repeated by constructing a multivariable logistic regression model that utilized patient category, mechanism of injury, composite injury severity score, total blood products transfused, prehospital heart rate and prehospital systolic pressure. Survival was compared between these groups using propensity matching. Results: Our search strategy yielded 28, 222 patients, 124 (0.4%) of whom received prehospital vasopressors. On univariable analysis vasopressor use was associated with lower odds of survival (OR 0.09, 0.06-0.13). The lower odds of survival persisted in the multivariate logistic regression model (OR 0.32, 0.18-0.56). Survival was lower among the vasopressor group (71.3%) when compared to a propensity matched cohort (94.3%). Conclusions: In this dataset, prehospital vasopressor use was associated with lower odds of survival. This finding persisted when adjusting for confounders and in a propensity matched cohort model.